(untitled) (TAJ: Journal of Teachers Association, 2023)
Background: Exclusive breastfeeding provides nutritional and immunological support for the normal growth and development of the infant. Bangladesh is traditionally a breastfed community. The probability of having an acute respiratory infection (ARI) episode was higher for formula-fed infants than fully breastfed infants during the first four months of life. The risks for partially breastfed infants fell between those of formula-fed and fully breastfed infants, suggesting a dose-response effect of breastfeeding on the risk of respiratory infection. Objective: This study compares exclusive, partial, and non-breastfed groups regarding the frequency and outcome of acute respiratory infection. Materials and methods: This cross-sectional comparative study was done at the Department of Pediatrics, Rajshahi Medical College Hospital, from January 2013 to June 2013, a period of six months. A total of 300 cases of infants suffering from ARI were selected. Among them, 100 are each for exclusive breastfed (EBF) babies, partially breastfed babies (PBF), and non-breastfed (NBF) babies. In addition, demographic profile, frequency, severity of attacks, outcomes, and length of hospital stay were assessed. Results: Most EBF babies came to the hospital with a history of one or two attacks of ARI, but PBF and NBF babies had multiple attacks. i.e., two, three, or more attacks. Most of the NBF and PBF have presented with severe attacks (84% and 72%, respectively), whereas only 42% of EBF babies presented with severe attacks; nonetheless, a maximum of 58% of EBF babies present with mild attacks. The severe attack is more frequent in the PBF and NBF groups than in the EBF groups. Conclusion: Frequency, severity, and hospital staying of ARI attacks are found to be more in the PBF and NBF group of babies than in EBF babies. Better outcomes were found in EBF group babies. TAJ 2022; 36: No-1: 135-141